Y=-4x+2/3

Simple and best practice solution for Y=-4x+2/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y=-4x+2/3 equation:



=-4Y+2/3
We move all terms to the left:
-(-4Y+2/3)=0
We get rid of parentheses
4Y-2/3=0
We multiply all the terms by the denominator
4Y*3-2=0
Wy multiply elements
12Y-2=0
We move all terms containing Y to the left, all other terms to the right
12Y=2
Y=2/12
Y=1/6

See similar equations:

| -7y-14=2y+22 | | 5-2x=4/2-4 | | 1/12+3/8y=5/12=5/8y | | -3x=-26 | | (8x-3)^2=0 | | 6x-8=55 | | 2/3=6/(q-4) | | 21-30x=0 | | -3-2v=-9v+17+11v | | 6x+8=55 | | 0.9/0.5=a/10a= | | -3-2v=-9v+17-11v | | 2(2x+1=-36 | | 9,000=x+1,000 | | -16=3x^2+15x-27 | | 90=5(6-4a) | | y=4*8+2 | | y=4*7+2 | | y=4*3+2 | | y=4*2+2 | | 1/14(x-9)=2/7(x+6)-1/7x= | | 3(8-8x)=144 | | 3/5=m/40 | | 52=13-d | | -(8m-3)+4=-4m+3 | | Y(y-7)=12 | | 6x+18=8x-9 | | 8=-2(3-t) | | 3(6x-5)+2x=4x-17+16x | | -4k+3=-5(k-3) | | 17-2x=26 | | 215x-30=15 |

Equations solver categories